Isolation and characterisation of Pink Pigmented Facultative Methylotrophs (PPFM) from Malaysian ulam leaves - Ramli, Nur Isti'anah; Abas, Faridah; Ismail, Intan Safinar; Rukayadi, Yaya; Jurime, Nuramiratul Hafizah (Journal of Pure and Applied Microbiology, 2024)
This study aims to isolate and characterise the Pink Pigmented Facultative Methylotrophs (PPFM) bacteria from the leaves of common Malaysian table salad (ulam). The colonies of PPFM bacteria were obtained using selectively modified Pseudomonas agar based on the appearance of the pink pigment colony. The three selected isolates labelled OJ4, OJ154 [Oenanthe javanica (Blume) DC.] and ML8 [from Melicope lunu-ankenda (Gaertn.) T. G. Hartley] were chosen for characterisation. The result showed the PPFM bacteria colonies (log CFU/g) at the leaf surface of C. caudatus are 4.4 ± 0.1, significantly higher than O. javanica, 3.8 ± 0.2, and M. lunu-ankenda, 3.2 ± 0.1. The selected isolates belong to the Gram-negative group, motile with rod shape with size [length (l) × width (w)] in µm unit 4.3 ± 1.1 × 1.6 ± 0.6, 5.4 ± 0.2 × 1.2 ± 0.1, and 3.5 ± 0.7 × 1.0 ± 0.0, respectively. They show positive urease, catalase, and oxidase activities, while none of them can degrade starch, gelatine, or cellulose, as well as glucose fermentation (MR test) and metabolism actions (VP test), producing indole and hydrogen sulphide gaseous. Only isolate OJ154 demonstrates positive casein hydrolysis and nitrate reduction activities, while only isolate ML8 can utilise citrate but not in lipid degradation. Their sequence analysis of the 16S rRNA indicated that OJ4 and ML8 are Methylobacterium radiotolerans with a similarity of 99%, whereas, OJ154 is Methylorubrum salsuginis with a similarity of 99%. To conclude, PPFM bacteria from the leaves of C. caudatus, O. javanica, and M. lunu-ankenda have been isolated and characterised in particular. © The Author(s) 2024. Open Access.